The importance of community policing: problem identification and dispute handling roles - HABETEGABRAEL, Dawit (Journal of Social Sciences)
Effective policing requires the active involvement of the local community. To engage the community, the Addis Ababa Police Commission implemented the community policy with the objectives of identifying inclusive problems in the community and managing social disputes. This study assessed the importance of the community policing program by using a qualitative research approach to collect detailed information. Qualitative data was collected through semi-structured interviews and focus group discussions. The study found that involving community residents in community policing helped police departments identify the problem and manage disputes at the community level. This enabled the resolution of critical and serious problems that require detailed police intervention. As a result of community engagement, beyond reducing the burden on the police department, empowering citizens in managing social disputes promotes a culture of proactive problem-solving among residents at the grassroots level. The study advocates for a review of conventional approaches by social work to empower communities to include citizen empowerment and empowerment programs to reduce structural barriers. Accordingly, the study suggests that the Addis Ababa Police Commission should intensively implement community policing in different divisions of the police commission.